One-pot synthesis and antimicrobial activity of new 4,6-disubstituted-3,4-dihydropyrimidine-2(1H)-thiones - Al-Refai, Mahmoud; Ibrahim, Mohammad; Al-Fawwaz, Abdullah; Geyer, Armin (European Journal of Chemistry, 2017)
A series of 3,4-dihydropyrimidine-2(1H)-thiones (3a-i) were synthesized in moderate yields via a one-pot reaction of 3-acetyl-2,5-diclorothiophene (1), aryl aldehydes (2a-i) and thiourea in methanolic solution of potassium hydroxide under reflux conditions. All newly synthesized compounds were characterized by extensive NMR analysis, including 1D NMR experiments (1H and 13C) and 2D NMR experiments (COSY, HMBC and HSQC), as well as ESI-MS and HRESI-MS data. The antimicrobial activity of all new compounds (3a-f) was tested against bacteria and fungi. Thione derivative (3c) only showed activity against Staphylococcus aureus, Bacillus subtilis and Aspergillus niger.